PENGARUH CITRA MEREK (BRAND IMAGE) DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT FIFGROUP POS SPEKTRA PEMATANGSIANTAR - Sriandani, Lili; Lie, Darwin; Efendi, Efendi; Halim, Fitria (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2018)
The purpose of this research is: 1) To determine the description of brand image, service quality, and customer’s satisfaction in PT FIFGroup Pos Spektra Pematangsiantar. 2) To determine the influence of brand image and service quality to customer’s satisfaction in PT FIFGroup Pos Spektra Pematangsiantar.Resultof research can be concluded as follows. 1) Brand Image,  service quality has been good, and customer’s satisfaction is also categorized satisfied. 2)The result is Ŷ = 11,560 + 0,363 X1 + 0,556 X2, meaning that there is positive and significant influence between the brand image and service quality to customer’s satisfaction. 3) The correlation result of r = 0,766, means that there are moderately high and positive correlation between brand image and service quality to the customer’s satisfaction. 4) The coefficient of determination R = 0,587 means that the level of customer’s satisfaction can be explained by the brand image and service quality 58,7%. 5)The research of hypothesis H0 is rejected, meaning that the brand image and the service quality positive and significant impact on customer’s satisfaction in PT FIFGroup Pos Spektra Pematangsiantar both simultaneously and partially. Keyword: Brand Image, Service Quality and Customer Satisfaction